A Study of autonomic nervous system dysfunction among patient with diabetes mellitus: a cross sectional study - Birajdar, Sidheshwar Virbhadraappa; Chavan, Sheshrao Sakharam; Munde, Sanjay A.; Bende, Yuvraj P. (International Journal of Advances in Medicine, 2017)
Background: Neuropathy is a common complication of diabetes mellitus and it may affect both the peripheral nerves and autonomic nervous system. It’s prevalence ranges from 1% to 90%. The present study is therefore designed to investigate autonomic nervous system involvement in diabetes mellitus by using simple bedside tests and to study its association with other diabetic angiopathies. Methods: 100 patients of diabetes mellitus were selected in the study. In Autonomic function tests for evaluating parasympathetic damage E: I ratio, 30:75 ratio and Valsalva ratio test was performed. Sympathetic damage was diagnosed by Blood pressure response to standing test and Blood pressure response to sustained handgrip test. Results: Abnormal E:I ratio was noticed in only 24 patients. The 30:15 ratio was found to be abnormal in 38 patients while the Valsalva Ratio was abnormal in 34 patients. Postural hypotension was observed in only 8% patients. The sustained hand grip test was abnormal in 10 patients. The prevalence of cardiac autonomic neuropathy was 58%. The association between the presence of autonomic neuropathy and peripheral neuropathy was statistically significant. However, the association between autonomic neuropathy and retinopathy and nephropathy was not statistically significant. Conclusions: The overall prevalence of autonomic neuropathy in diabetes mellitus was 58%. There was parasympathetic preponderance over sympathetic nervous system in the involvement of diabetic autonomic neuropathy. There was statistically significant association of diabetic autonomic neuropathy with peripheral neuropathy as compared to retinopathy and nephropathy.